Business Report : TIZ 6938 - Final Project and Internal Industrial Internship - Norhayati, Hashim (College of Arts and Sciences, 2008)
The report is about Myriad Solutions Sdn Bhd, an ICT Company. The report consist of Company Profile, business plan 'teleworking', sales achievement report and company's future plan.